Refeeding hypophosphataemia in a Malaysian intensive care unit: incidence, risk factors and outcomes - Md Ralib, Azrina; Mat Nor, Mohd Basri; Ismail, Che Ainun Nasihah; Hassan, Muhammad Zul Hilmi; Tuan Ibrahim, Tuan Muhd Fahmi (Ministry of Health and Universiti Brunei Darussalem, 2015)
Introduction: Refeeding syndrome is characterised by acute electrolyte derangement following the start of nutrition. Hypophosphataemia is the predominant feature of the electrolyte derangement, hence commonly used for its definition. We aim to assess the incidence of refeeding hypophosphataemia, and its associated risk factors, and outcome in our local ICU. Materials and Methods: This was a single centre, prospective observational study at the ICU of Hospital Tengku Ampuan Afzan Kuantan, involving adult admission longer than 48 hours. Chronic renal failure patients and those receiving dialysis were excluded. Refeeding hypophosphataemia (RH) was considered if plasma phosphate was less than 0.65 mmol/l. Results: Fifty-four patients were screened. After exclusion, 29 were recruited, of which, 13 (44.8%) patients had RH. Of this, 66% occurred with duration of fasting of less than two days. These patients had higher NUTRIC score (3.9 ± 2.1 versus 2.4 ± 1.9, p=0.05). There was a trend of lower albumin, magnesium, calcium and potassium concentration, however these were not statistically significant. All patients with hypomagnesaemia (less than 0.5 mmol/l) had RH (p=0.01). There were no differences in mortality, length of hospital or ICU stay and duration of mechanical ventilation. Conclusion: Refeeding hypophosphataemia is common, occurring in 45% of ICU admission regardless of their fasting status. Higher NUTRIC score and hypomagnesaemia were the risk factors, however we showed no differences in outcome. Future larger studies could evaluate the association between its risk factors and outcome in our local population.